Synthesis and iron coordination properties of schizokinen and its imide derivative - Hataichanok Chuljerm (2020)
This journal is © The Royal Society of Chemistry. The iron(iii) affinity constants for schizokinen and its imide derivative are reported for the first time. Surprisingly, schizokinen possesses a higher affinity for iron(iii) than desferrioxamine B; log KFeIII (FeL), 36.2 and 30.6, respectively. This increase in value is associated with the substitution of one hydroxamate function by an α-hydroxycarboxylate grouping. By virtue of the similarity of siderophore-iron(iii) complexes and siderophore-gallium(iii) complexes, schizokinen (which is a Gram positive siderophore) has potential for 68Ga PET-based imaging.